Differences in the insulin counterregulatory hormones between obese and nonobese male patients with type 2 diabetes mellitus - Rong Huang; Yujie Bao; Yuanli Xiong; Jianhua Ma; Bo Ding (Scientific Reports)
Abstract Obesity is associated with both high and low levels of hypoglycemia, and impairment of counterregulatory hormones may predispose individuals to hypoglycemia. This study aimed to explore differences in the responsiveness of insulin counterregulatory hormones to hypoglycemia between men with or without obesity who have been newly diagnosed with type 2 diabetes mellitus (T2DM). This study enrolled 25 men newly diagnosed with T2DM who were hospitalized in the Department of Endocrinology and Metabolism between January 2022 and December 2022. All participants were treated with intensive insulin pump therapy to achieve glycemic control within one week, then a hyperinsulinemic-hypoglycemic clamp was used to evaluate insulin counter-regulatory hormones for hypoglycemia. Based on the body mass index, 10 and 15 patients were included in the obese and nonobese groups, respectively. During the hyperinsulinemic-hypoglycemic clamp test, the obese group showed a significant lower multiple of adrenocorticotropic hormone elevation than the nonobese group (P = 0.040). Regarding the proportion of hormone response multiples reaching the target, those who reached the reaction multiple were lower in the obese group than those in the non-obese group, although the differences were not statistically significant (all P > 0.05). The responses of insulin counterregulatory hormones to hypoglycemia in men with obesity and newly diagnosed T2DM were significantly lower than those in men with T2DM but without obesity.